“I Was Something You Pick Up and Take a Swig of”: Ecofeminist Toxic Discourse in Jennifer Clement’s Prayers for the Stolen - Morysová, Anežka; Beneš, Jan (American & British Studies Annual, 2025)
Echoing ecofeminism’s long-standing concerns with the interconnection between the oppression of women and the degradation of the environment as a consequence of patriarchal and capitalist systems, this paper suggests that Jennifer Clement’s acclaimed novel Prayers for the Stolen (2014) should be read as representative of an ecofeminist toxic discourse, which enables the oppressed, where weak women characters find agency in telling their story and drawing attention to the multi-layered toxicity they have had to face. Such a reading not only highlights the novel’s preoccupation with and warning against pollution, toxicity, and overall environmental degradation – thus far explored by few scholars of Clement’s work – but also illuminates the inescapable connections Clement repeatedly draws between how nature and women are physically and mentally abused and poisoned by the same toxic patriarchal and capitalist forces.